Effects of Sport Teaching on Students' Enjoyment and Fun: A Systematic Review and Meta-Analysis - Rodríguez Macías, Manuel; Abad Robles, Manuel Tomás; Giménez Fuentes-Guerra, Francisco Javier (Frontiers in Psychology, 2021)
The methodology used in sport teaching influences not only the students' technical and tactical learning, but also psychological and social dimensions such as enjoyment. We aimed to analyze the effects of interventions using conventional and non-conventional sport teaching methodology on students' enjoyment/fun, through a systematic review and meta-analysis. The search was carried out following the PRISMA Statement in the databases of Web of Science, PubMed, Scopus, SportDiscus, Eric and PsycInfo. A total of 1,481 documents were obtained, with the addition of 5 more which were identified in the reference lists of the articles found in the databases. Eleven articles were considered to meet the inclusion criteria. The meta-analysis yielded a moderate effect size of 0.72, and a 95% CI from 0.48 to 0.96 in favor of non-conventional teaching methods, highlighting the model of sports education. Nevertheless, the heterogeneity of the interventions was large and the quality of the evidence, according to GRADE, was very low. In conclusion, the use of non-conventional models in sport teaching with the aim of increasing the enjoyment/fun of boys and girls is advised. These suggestions could be useful for teachers and sport coaches to increase the enjoyment/fun of their trainees during sport practice.